Surgical management of pancreatic cancer liver oligometastases. (May 2022) - Macfie, Rebekah; Berger, Yael; Sarpel, Umut; Hiotis, Spiros; Golas, Benjamin; Labow, Daniel; Cohen, Noah
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer, which commonly metastasizes to the liver. The current standard of care for metastatic PDAC is systemic chemotherapy, however there are limited emerging data regarding surgical resection of pancreatic oligometastases in select patients. Here we review the literature addressing resection of PDAC liver oligometastases. Highlights: Pancreatic ductal adenocarcinoma (PDAC) commonly metastasizes to the liver. We review the data regarding resection of pancreatic liver oligometastases. There may be a role for selective metastaectomy, however further study is required.